Steroids, Pregnancy and Fetal Development - Solano, Maria Emilia; Arck, Petra Clara (Frontiers in Immunology, 2020)
Maternal glucocorticoids critically rise during pregnancy reaching up to a twenty-fold increase of mid-pregnancy concentrations. Concurrently, another steroid hormone, progesterone, increases. Progesterone, which shows structural similarities to glucocorticoids, can bind the intracellular glucocorticoid receptor, although with lower affinity. Progesterone is essential for the establishment and continuation of pregnancy and it is generally acknowledged to promote maternal immune tolerance to fetal alloantigens through a wealth of immunomodulatory mechanisms. Despite the potent immunomodulatory capacity of glucocorticoids, little is known about their role during pregnancy. Here we aim to compare general aspects of glucocorticoids and progesterone during pregnancy, including shared common steroidogenic pathways, plasma transporters, regulatory pathways, expression of receptors, and mechanisms of action in immune cells. It was recently acknowledged that progesterone receptors are not ubiquitously expressed on immune cells and that pivotal features of progesterone induced- maternal immune adaptations to pregnancy are mediated via the glucocorticoid receptor, including e.g. T regulatory cells expansion. We hypothesize that a tight equilibrium between progesterone and glucocorticoids is critically required and recapitulate evidence supporting that their disequilibrium underlie pregnancy complications. Such a disequilibrium can occur, e.g. after maternal stress perception, which triggers the release of glucocorticoids and impair progesterone secretion, resulting in intrauterine inflammation. These endocrine misbalance might be interconnected, as increase in glucocorticoid synthesis, e.g. upon stress, may occur in detriment of progesterone steroidogenesis, by depleting the common precursor pregnenolone. Abundant literature supports that progesterone deficiency underlies pregnancy complications in which immune tolerance is challenged. In these settings, it is largely yet undefined if and how glucocorticoids are affected. However, although progesterone immunomodulation during pregnancy appear to be chiefly mediated glucocorticoid receptors, excess glucocorticoids cannot compensate by progesterone deficiency, indicating that additional und still undercover mechanisms are at play.